(untitled) - Josephson, Matthew (New York, 1959)
In his 84 years, Thomas Edison acquired a record number of 1,093 patents (singly or jointly) and was the driving force behind such innovations as the phonograph, the incandescent light bulb and one of the earliest motion picture cameras. He also created the world’s first industrial research laboratory. Known as the “Wizard of Menlo Park,” for the New Jersey town where he did some of his best-known work, Edison had become one of the most famous men in the world by the time he was in his 30s. In addition to his talent for invention, Edison was also a successful manufacturer and businessman who was highly skilled at marketing his inventions–and himself–to the public.
Keywords: Nhà phát minh,Inventors; Tiểu sử,Biography; Hoa Kỳ,United States